Use sonoelastography to predict the reparability of large-to-massive rotator cuff tears. Issue 27 (2nd July 2020) - Tseng, Yu-Hsuan; Chou, Wen-Yi; Wu, Kuan-Ting; Chang, Ching-Di; Chen, Yi-Cun; Huang, Yu-Chi; Lin, Wei-Che; Chen, Po-Cheng
Abstract: Introduction: Most symptomatic large-to-massive rotator cuff tears (RCTs) should be operated, but the surgical reparability depended on the degree of rotator cuff muscle atrophy or fatty infiltration. The orthopedic surgeons will decide whether the teared stump is reparable during the surgery, but preoperative evaluation can be done by some assessment tools. Magnetic resonance imaging (MRI) was used in recent studies to predict the reparability of large-to-massive RCTs, but the clinical availability was not as good as ultrasound. We hypothesize that the ultrasound elastography can predict the reparability of large-to-massive RCTs. Methods: This is a prospective observational study and participants with large-to-massive RCTs who are going to have surgeries will be included. Out investigators will evaluate the shoulder passive range of motion (ROM) and strength of all participants. Participants' degree of shoulder pain and activities of daily living (ADLs) will be assessed by American Shoulder and Elbow Surgeons (ASES) score. The ultrasound elastography will be used to evaluate the tissue quality of supraspinatus muscle and infraspinatus muscle. To test the reliability of the ultrasound elastography, two physicians will perform the ultrasound elastography independently and twenty participants will be selected for the reliability test. Besides, MRI will be used to evaluate the size of tear, the degree of tendon retraction, fatty infiltration of rotator cuff muscles, and muscle atrophy. Finally, the orthopedic surgeons will perform surgeries and decide whether the teared stump can be completely repaired intraoperatively. The primary analysis is the predictive validity of ultrasound elastography for the reparability of large-to-massive RCTs. Before the predictive validity of ultrasound elastography is measured, our investigators will assess the reliability of ultrasound elastography when administered to cases with large-to-massive RCTs, and we will check the correlations between the findings of ultrasound elastography and MRI. Discussion: The outcome will provide the evidence of ultrasound elastography for preoperative evaluation of large-to-massive RCTs. The relationships between the findings of ultrasound elastography and MRI will also be examined for further analysis. Trial registration: Clinicaltrials.gov NCT03682679. Date of Registration: 25 September 2018, https://clinicaltrials.gov/ct2/show/NCT03682679?cond=rotator+cuff&cntry=TW&draw=2&rank=1 .